2016
DOI: 10.3389/fmicb.2016.00421
|View full text |Cite
|
Sign up to set email alerts
|

Red Seaweeds Sarcodiotheca gaudichaudii and Chondrus crispus down Regulate Virulence Factors of Salmonella Enteritidis and Induce Immune Responses in Caenorhabditis elegans

Abstract: Red seaweeds are a rich source of unique bioactive compounds and secondary metabolites that are known to improve human and animal health. S. Enteritidis is a broad range host pathogen, which contaminates chicken and poultry products that end into the human food chain. Worldwide, Salmonella outbreaks have become an important economic and public health concern. Moreover, the development of resistance in Salmonella serovars toward multiple drugs highlights the need for alternative control strategies. This study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 62 publications
(72 reference statements)
0
34
0
2
Order By: Relevance
“…Chondrus crispus supplemented feed was effective in reducing S. Enteritidis count in the excreta and contents of the ceca. This could be due to the ability of seaweed to block the initial attachment of bacteria to the epithelial cells by targeting the motility and virulence of S. Enteritidis (Kulshreshtha et al, 2016). Furthermore, none of the egg yolk samples were positive for S. Enteritidis in the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrus crispus supplemented feed was effective in reducing S. Enteritidis count in the excreta and contents of the ceca. This could be due to the ability of seaweed to block the initial attachment of bacteria to the epithelial cells by targeting the motility and virulence of S. Enteritidis (Kulshreshtha et al, 2016). Furthermore, none of the egg yolk samples were positive for S. Enteritidis in the trial.…”
Section: Discussionmentioning
confidence: 99%
“…QS have been corroborated as one of the crucial factor responsible for host mortality in the C. elegans slow killing assay (Papaioannou et al, 2009). Elsewhere, a marine seaweed extract was reported to repress P. aeruginosa QS genes, leading to diminished production of virulence factors and survival of infected worms (Kulshreshtha et al, 2016). Future work should ascertain the capacities of H. atra metabolites in interfering with pivotal elements of the P. aeruginosa QS.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse marine environment impose the selection of an array of metabolites produced by an immeasurable source of organisms (Molinski et al, 2009). Secondary metabolites with anti-infective properties against P. aeruginosa have been identified from numerous marine organisms including marine bacteria and seaweeds (Fatin et al, 2017; Kandasamy et al, 2012; Kulshreshtha et al, 2016; Liu et al, 2013; Naik et al, 2013; Papa et al, 2015). To date, the only published report of an anti-infective from marine invertebrates using the C. elegans platform is from a tropical mollusk (Kong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the protective effect of C. crispus extract was diminished in selected C. elegans mutants ( pmk-1 , daf-2 , daf-16 , or skn-1 ), implying that the effect from the host perspective is mediated via the highly conserved immune pathways. Likewise, concurrent virulence inhibitory and immunostimulatory effects have also been observed in other seaweed-related natural products, including Tasco ® , a commercially available animal feed supplement made from the brown seaweed Ascophyllum nodosum (Kandasamy et al, 2012) and another red seaweed species Sarcodiotheca gaudichaudii (Kulshreshtha et al, 2016). Both, S. gaudichaudii and C. crispus extracts disarmed the pathogenicity of Salmonella enteritidis by reducing biofilm formation, swimming and swarming motility and down-regulating expression of virulence and quorum sensing genes in S. enteritidis.…”
Section: Identification Of Novel Anti-infectivesmentioning
confidence: 98%
“…Both, S. gaudichaudii and C. crispus extracts disarmed the pathogenicity of Salmonella enteritidis by reducing biofilm formation, swimming and swarming motility and down-regulating expression of virulence and quorum sensing genes in S. enteritidis. These extracts also reduced the intestinal bacterial load in C. elegans by promoting the expression of host immune response genes encoding lectin-family, saponin-like and antibacterial proteins (Kulshreshtha et al, 2016). Whilst no direct evidence of seaweed extract exerting an immunomodulatory effect on animal infection-directed immune responses, is available, Luo et al (2015) demonstrated that seaweed polysaccharide was immunomodulatory in a cell-culture based assay as well as in a mouse tumor model.…”
Section: Identification Of Novel Anti-infectivesmentioning
confidence: 99%